Precision motion control of X-ray optics assisted with optical interferometric metrology for advanced X-ray beam sources - Ting Guo; Jennifer Lien (Light: Advanced Manufacturing)
Nanoradian precision has been achieved in control of X-ray optics using feedback from optical interferometric measurements and real time adjustments of three mirrors in a simulated X-ray laser cavity in recent work reported by Koehlenbeck et al.